Method for producing optical laminate

By adopting specific lamination steps and holding conditions in the manufacturing process of the optical laminate, the problem of wrinkle defects during bending of the optical laminate is solved, and bending stability under the condition of a small curvature radius is achieved.

CN114846371BActive Publication Date: 2025-03-07SUMITOMO CHEM CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080087282.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-23
Filing Date
2020-11-11
Publication Date
2025-03-07
Estimated Expiration
2040-11-11

AI Technical Summary

Technical Problem

The existing optical laminates are prone to fine wrinkle defects when bending, especially under the conditions of small curvature radius, and it is difficult to avoid the occurrence of wrinkle defects.

Method used

In the manufacturing process of the optical laminate, specific lamination steps and holding conditions are adopted, including laminating the optical film, the active energy ray curable adhesive layer and the phase difference layer, and maintaining it under specific temperature and vibration conditions, ensuring close contact and stable curing of the cured adhesive layer and the phase difference layer.

Benefits of technology

It is realized that even under the condition of a small curvature radius, it is difficult to generate wrinkle defects, and the bending stability and performance of the optical laminate are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114846371B_ABST
    Figure CN114846371B_ABST
Patent Text Reader

Abstract

Provided is a method for manufacturing an optical laminate having an optical film and a phase difference layer of a cured layer containing a polymerizable liquid crystal compound, wherein wrinkle defects are unlikely to occur even when the laminate is bent with a small radius of curvature. In the method for manufacturing an optical laminate, the optical laminate sequentially comprises an optical film, a cured adhesive layer which is a cured layer of an active energy ray-curable adhesive, and a phase difference layer which is a cured layer containing a polymerizable liquid crystal compound, and the manufacturing method comprises the following steps in the following order: a step of laminating the optical film, the active energy ray-curable adhesive layer, and the phase difference layer so that the active energy ray-curable adhesive layer and the phase difference layer are in contact with each other; a step of maintaining the optical laminate under conditions that satisfy any one of (1) maintaining the optical laminate at a temperature of 30° C. or higher for more than 2 hours, (2) maintaining the optical laminate under vibration conditions for more than 2 hours, and (3) maintaining the optical laminate for more than 48 hours; and a step of curing the active energy ray-curable adhesive layer to form a cured adhesive layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing an optical layered body and also to an optical layered body. Background Art

[0002] In image display devices such as organic EL display devices, an optical laminate (elliptical polarizing plate) combining a polarizer (linear polarizer) and a phase difference layer is sometimes used for the purpose of preventing external light reflection caused by a metal electrode. For example, in Japanese Unexamined Patent Publication No. 2018-017996 (Patent Document 1), it is described that a polarizer and a phase difference layer formed of a polymerizable liquid crystal compound are laminated via an ultraviolet curable adhesive layer, and the adhesive layer is cured by ultraviolet irradiation to produce an elliptical polarizing plate.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-017996 Summary of the invention

[0006] Problems to be solved by the invention

[0007] Regarding the existing optical laminate produced by bonding an optical film including a polarizer and a phase difference layer formed by a polymerizable liquid crystal compound using an active energy ray-curable adhesive or a pressure-sensitive adhesive, if the existing optical laminate is bent so that the radius of curvature gradually decreases, there is a tendency that fine wrinkles (hereinafter also referred to as "wrinkle defects") are easily generated in the phase difference layer even at a relatively large radius of curvature. In the case of considering the application to a bendable and further bendable image display device, etc., it is desired that the optical laminate is difficult to generate wrinkle defects even when it is bent with a small radius of curvature.

[0008] The present invention provides an optical laminate, and a method for producing the same, comprising an optical film and a phase difference layer including a cured layer of a polymerizable liquid crystal compound, wherein wrinkle defects are unlikely to occur even when the laminate is bent with a small radius of curvature.

[0009] Means for solving problems

[0010] The present invention provides a method for producing an optical layered body and an optical layered body described below.

[0011] [1] A method for manufacturing an optical laminate, wherein the optical laminate comprises, in sequence, an optical film, a cured adhesive layer which is a cured layer of an active energy ray-curable adhesive, and a phase difference layer which is a cured layer of a polymerizable liquid crystal compound, the manufacturing method comprising the following steps in the following order: a step of stacking the optical film, the active energy ray-curable adhesive layer, and the phase difference layer so that the active energy ray-curable adhesive layer and the phase difference layer are in contact with each other; a step of maintaining the optical film under any one or more of the following (1) to (3): (1) maintaining the optical film at a temperature of 30° C. or higher for more than 2 hours, (2) maintaining the optical film under vibration conditions for more than 2 hours, and (3) maintaining the optical film at a temperature of 30° C. or higher for more than 2 hours, and (3) maintaining the optical film at a temperature of 48 hours or higher; and a step of curing the active energy ray-curable adhesive layer to form the cured adhesive layer.

[0012] [2] A method for manufacturing an optical laminate, wherein the optical laminate comprises, in sequence, an optical film, a cured adhesive layer which is a cured layer of an active energy ray-curable adhesive, and a phase difference layer which is a cured layer of a polymerizable liquid crystal compound, the manufacturing method comprising the following steps in the following order: a step of preparing a laminate comprising a substrate film and the phase difference layer laminated in contact with the substrate film; a step of peeling the substrate film from the phase difference layer at a peeling speed of 50 m / min or more; a step of laminating an optical film on the peeled surface of the phase difference layer after the substrate film is peeled off, via the active energy ray-curable adhesive layer; and a step of curing the active energy ray-curable adhesive layer to form the cured adhesive layer.

[0013] [3] The method for producing an optical layered body according to [1] or [2], wherein the optical film includes a linear polarizer.

[0014] [4] The method for producing an optical laminate according to [3], wherein in the lamination step, the optical film, the active energy ray-curable adhesive layer and the phase difference layer are laminated so that the linear polarizer and the active energy ray-curable adhesive layer are in contact with each other.

[0015] [5] An optical laminate comprising, in order, an optical film, a cured adhesive layer which is a cured layer of an active energy ray-curable adhesive, and a phase difference layer which is a cured layer of a polymerizable liquid crystal compound, wherein the cured adhesive layer and the phase difference layer are in contact with each other, and a surface of the phase difference layer on the side of the cured adhesive layer satisfies any one or more of the following (a) to (d):

[0016] (a) Arithmetic mean roughness Sa is 0.065 μm or more,

[0017] (b) The root mean square height Sq is 0.085 μm or more,

[0018] (c) the interface development area ratio Sdr is 0.2% or more,

[0019] (d) The root mean square tilt Sdq is greater than or equal to 0.065.

[0020] [6] The optical layered body according to [5], wherein the optical film includes a linear polarizer.

[0021] [7] The optical laminate according to [6], wherein the linear polarizer and the cured adhesive layer are in contact with each other.

[0022] Effects of the Invention

[0023] The present invention can provide an optical laminate comprising an optical film and a phase difference layer including a cured layer of a polymerizable liquid crystal compound, which is unlikely to cause wrinkle defects even when bent with a small radius of curvature, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a schematic cross-sectional view showing an example of the layer structure of a laminate obtained by the lamination step in the first embodiment.

[0025] Figure 2 It is a schematic cross-sectional view showing an example of the layer structure of the optical layered body.

[0026] Figure 3 This is a schematic cross-sectional view showing an example of the layer structure of the laminated body prepared in the preparation step in the second embodiment.

[0027] Figure 4 This is a schematic cross-sectional view showing an example of the layer structure of a linear polarizing plate.

[0028] Figure 5 It is a schematic cross-sectional view showing an example of the layer structure of the phase difference laminate.

[0029] Figure 6 It is a schematic cross-sectional view showing another example of the layer structure of the optical layered body.

[0030] Figure 7 It is a schematic cross-sectional view showing still another example of the layer structure of the optical layered body.

[0031] Figure 8 It is a schematic diagram explaining the evaluation method of wrinkle defects.

[0032] Fig. 9 It is a schematic diagram for explaining the directions of the absorption axis and the slow axis in the optical layered body. DETAILED DESCRIPTION

[0033] <Method for producing an optical laminate>

[0034] The optical laminate manufactured by the manufacturing method involved in the present invention comprises an optical film, a cured adhesive layer which is a cured layer of an active energy ray-curable adhesive (hereinafter simply referred to as a "cured adhesive layer"), and a phase difference layer which is a cured layer containing a polymerizable liquid crystal compound (hereinafter simply referred to as a "phase difference layer") in this order.

[0035] The optical layered body produced by the production method according to the present invention can be suitably used in image display devices such as organic EL display devices.

[0036] Embodiments of the method for producing an optical laminate according to the present invention will be described below with reference to the accompanying drawings. The embodiments described below can be combined arbitrarily. The accompanying drawings are schematic diagrams and may not represent actual dimensions.

[0037] In each embodiment shown below, a long strip may be used as the film or layer used in each process and each process may be performed continuously, or a single piece may be used as the film or layer used in each process and each process may be performed discontinuously. The single piece is obtained by cutting a long strip.

[0038] [Implementation Method 1]

[0039] The method for producing the optical layered body according to the present embodiment includes the following steps in the order described.

[0040] A step of laminating the optical film, the active energy ray-curable adhesive layer, and the phase difference layer including a cured layer of a polymerizable liquid crystal compound so that the active energy ray-curable adhesive layer and the phase difference layer are in contact with each other (laminating step);

[0041] A step of maintaining the material under the conditions of satisfying any one or more of the following (1) to (3) (maintaining step):

[0042] (1) Keep at a temperature above 30°C for more than 2 hours,

[0043] (2) Maintain under vibration conditions for more than 2 hours,

[0044] (3) Maintained for more than 48 hours; and

[0045] A step of curing the active energy ray-curable adhesive layer to form a cured adhesive layer (curing step).

[0046] 〔1〕Lamination process

[0047] Figure 1: is a schematic cross-sectional view showing an example of the layer structure of the laminate obtained by the lamination process in this embodiment. The lamination process is a process of laminating the optical film 10 and the phase difference layer 30 via the active energy ray curable adhesive layer 20 (hereinafter simply referred to as "adhesive layer"). In this specification, the so-called active energy ray curable adhesive layer refers to a layer composed of an active energy ray curable adhesive. As the active energy ray curable adhesive, an adhesive having the ability to bond the phase difference layer 30 and the optical film 10 is used.

[0048] In the lamination step, the optical film 10, the adhesive layer 20, and the phase difference layer 30 are laminated so that the adhesive layer 20 is in contact with the phase difference layer 30. Preferably, the optical film 10, the adhesive layer 20, and the phase difference layer 30 are laminated so that the adhesive layer 20 is in contact with the phase difference layer 30.

[0049] The lamination step can be performed by forming an adhesive layer 20 on one or more surfaces selected from the adhesive surface of the optical film 10 and the adhesive surface of the phase difference layer 30, and laminating the optical film 10 and the phase difference layer 30 via the adhesive layer 20. The adhesive layer 20 can be formed by applying an active energy ray-curable adhesive to the adhesive surface by a known coating method.

[0050] In the laminated body obtained by the lamination process, the thickness of the adhesive layer 20 is usually greater than 0.5 μm and less than 50 μm. From the viewpoint of suppressing wrinkle defects, the viewpoint of adhesion between the optical film 10 and the phase difference layer 30, and the viewpoint of thinning the obtained optical laminated body, it is preferably greater than 1 μm and less than 30 μm, and more preferably greater than 2 μm and less than 20 μm.

[0051] Before forming the adhesive layer 20, one or more surfaces selected from the bonding surface of the optical film 10 and the bonding surface of the phase difference layer 30 may be subjected to a surface activation treatment such as plasma treatment, corona treatment, ultraviolet irradiation treatment, flame treatment, or saponification treatment. The surface activation treatment can improve the adhesion between the optical film 10 and the phase difference layer 30.

[0052] The optical film 10 may be a film of a single-layer structure or a film of a multi-layer structure. Examples of the optical film 10 include a linear polarizing plate and the like.

[0053] In this specification, the linear polarizing plate refers to an optical element including at least a linear polarizing plate, and may include a linear polarizing plate and a thermoplastic resin film bonded to at least one surface thereof.

[0054] When the optical film 10 is a linear polarizing plate, in the laminate obtained by the lamination step, the linear polarizer included in the linear polarizing plate and the adhesive layer 20 are preferably in contact with each other.

[0055] The optical film 10 and the active energy ray-curable adhesive will be described in more detail in the section of <Optical laminate> to be described later.

[0056] The phase difference layer 30 includes a cured layer of a polymerizable liquid crystal compound and exhibits optical anisotropy according to the type of the liquid crystal compound used to form the layer. Hereinafter, the cured layer of the polymerizable liquid crystal compound is also referred to as a "phase difference expressing layer".

[0057] In the present specification, the phase difference layer 30 may be composed of a phase difference expressing layer, or may include a phase difference expressing layer and an orientation layer.

[0058] In the lamination process, the phase difference layer 30 bonded to the optical film 10 via the adhesive layer 20 may be pre-stacked with one or more other layers before the lamination process. For example, a phase difference layer laminate including the phase difference layer 30 and other phase difference layers may be pre-made, and the phase difference layer laminate may be bonded to the optical film 10 via the adhesive layer 20.

[0059] The retardation layer, the retardation expressing layer, the orientation layer, the retardation layer laminate, and the like will be described in more detail in the section of <Optical laminate> to be described later.

[0060] 〔2〕Maintaining process

[0061] The holding step is a step of holding the stacked body obtained in the stacking step under specific conditions.

[0062] The specific method for maintaining the laminate is not particularly limited, and may be, for example, leaving the laminate at rest under the specific conditions described above.

[0063] The above-mentioned specific conditions refer to satisfying any one or more of the following conditions (1) to (3):

[0064] (1) Keep at a temperature above 30°C for more than 2 hours,

[0065] (2) Maintain under vibration conditions for more than 2 hours,

[0066] (3) Maintain for more than 48 hours.

[0067] According to the manufacturing method according to the present embodiment including the laminating step and the holding step, it is possible to manufacture an optical layered body that is unlikely to suffer from wrinkle defects even when bent with a small radius of curvature. This is presumably due to the following reasons.

[0068] The phase difference layer 30 is brought into contact with the adhesive layer 20 before curing by the lamination process, and this state is maintained under the above-mentioned specific conditions in the subsequent holding process. The active energy ray-curable adhesive before curing exerts adhesive force on the phase difference layer 30 after curing, so it can be seen that it interacts with the phase difference layer 30. It is believed that if the active energy ray-curable adhesive that interacts with the phase difference layer 30 continues to be in contact with the phase difference layer 30 under the above-mentioned specific conditions, the contact surface ( Figure 1 The rough surface of the phase difference layer 30 improves the adhesion with the adhesive layer 20.

[0069] When the adhesion is improved, the cured adhesive layer (adhesive layer after curing) and the phase difference layer 30 are deformed integrally when the optical laminate is bent, and thus it is considered that the occurrence of wrinkle defects is easily suppressed.

[0070] The production method according to the present embodiment is also advantageous in suppressing rainbow unevenness described below in the obtained optical layered body.

[0071] The holding temperature in the above condition (1) is 30° C. or higher, preferably 35° C. or higher, more preferably 38° C. or higher, and further preferably 40° C. or higher from the viewpoint of more effectively suppressing the occurrence of wrinkle defects. The holding temperature is usually 55° C. or lower, and preferably 50° C. or lower in order to reduce the change in the water content after the holding step.

[0072] The holding time in the above condition (1) also depends on the holding temperature, but is usually 2 hours or more. From the viewpoint of more effectively suppressing the occurrence of wrinkle defects, it is preferably 3 hours or more, more preferably 4 hours or more, and even more preferably 5 hours or more. The holding time also depends on the holding temperature, but usually less than 48 hours is sufficient. Alternatively, the holding time may be 48 hours or more, but in this case, the holding step satisfies the conditions (1) and (3).

[0073] The vibration imparted to the laminate in the above condition (2) can be performed, for example, by placing the laminate on a vibration source. The vibration source is not particularly limited as long as it can vibrate at a fixed period and a fixed amplitude, and a vibration generator can be used, and a rotating device such as an electric motor that can rotate at a fixed speed can be used, and a transformer that can pass an alternating current can also be used.

[0074] The frequency of the vibration is preferably 5 Hz or more, more preferably 10 Hz or more, from the viewpoint of suppressing the occurrence of wrinkle defects. The frequency of the vibration is preferably 50 Hz or less, more preferably 40 Hz or less, from the viewpoint of suppressing the occurrence of so-called floating, in which the layers constituting the laminate are partially peeled off from each other.

[0075] The amplitude of the vibration is preferably 0.5 mm or more, more preferably 1 mm or more, from the viewpoint of suppressing the occurrence of wrinkle defects. The amplitude of the vibration is preferably 30 mm or less, more preferably 10 mm or less, from the viewpoint of suppressing the occurrence of so-called floating in which the layers constituting the laminate are partially peeled off from each other.

[0076] The holding temperature in the above condition (2) is not particularly limited, and is usually 5°C or higher. From the viewpoint of more effectively suppressing the occurrence of wrinkle defects, it is preferably 10°C or higher, more preferably 15°C or higher, and even more preferably 20°C or higher. The holding temperature may be 30°C or higher, but in this case, the holding process satisfies the conditions (1) and (2). The holding temperature is usually 55°C or lower, and is preferably 50°C or lower because it can also reduce the change in the water content after the holding process.

[0077] The holding time in the above condition (2) also depends on the holding temperature, but is usually 2 hours or more. From the viewpoint of more effectively suppressing the occurrence of wrinkle defects, it is preferably 3 hours or more, more preferably 4 hours or more, and even more preferably 5 hours or more. The holding time also depends on the holding temperature, but usually less than 48 hours is sufficient. Alternatively, the holding time may be 48 hours or more, but in this case, the holding step satisfies the conditions (2) and (3).

[0078] The holding temperature in the above condition (3) is not particularly limited, but is usually 5°C or higher, preferably 10°C or higher, more preferably 15°C or higher, and even more preferably 20°C or higher from the viewpoint of more effectively suppressing the occurrence of wrinkle defects. The holding temperature may be 30°C or higher, but in this case, the holding process satisfies the conditions (1) and (3). The holding temperature is usually 55°C or lower, and is preferably 50°C or lower from the viewpoint of reducing the change in the water content even after the holding process is completed.

[0079] The holding time in the above condition (3) also depends on the holding temperature, but is usually 48 hours or more, preferably 54 hours or more, more preferably 66 hours or more, and even more preferably 72 hours or more from the viewpoint of more effectively suppressing the occurrence of wrinkle defects. The holding time also depends on the holding temperature, but usually 120 hours or less is sufficient.

[0080] Under any of the conditions (1) to (3) above, the relative humidity of the environment in which the laminate is maintained is, for example, 20% RH or more and 80% RH or less, preferably 30% RH or more and 70% RH or less.

[0081] 〔3〕Curing process

[0082] refer to Figure 2 In this step, the adhesive layer 20 is cured by irradiation with active energy rays to form a cured adhesive layer 20a, thereby obtaining an optical laminate. The type of active energy rays irradiated is appropriately selected according to the induction wavelength of the curable component contained in the active energy ray-curable adhesive constituting the adhesive layer 20. The active energy rays are preferably ultraviolet rays.

[0083] [Implementation Method 2]

[0084] The method for producing the optical layered body according to the present embodiment includes the following steps in the order described.

[0085] A step of preparing a laminate including a substrate film and a phase difference layer laminated in contact with the substrate film (preparation step);

[0086] A step of peeling the base film from the phase difference layer at a peeling speed of 50 m / min or more (peeling step);

[0087] A step of laminating an optical film on the peeled surface of the phase difference layer after peeling off the base film via an active energy ray-curable adhesive layer (laminating step); and

[0088] A step of curing the active energy ray-curable adhesive layer to form a cured adhesive layer (curing step).

[0089] 〔1〕Preparation process

[0090] As described above, the phase difference layer 30 includes a phase difference expression layer (a cured layer of a polymerizable liquid crystal compound), and may consist of a phase difference expression layer, or may include a phase difference expression layer and an orientation layer. Therefore, the laminated body including a substrate film and a phase difference layer stacked in contact with the substrate film prepared in this step may have a layer structure of, for example, a substrate film / orientation layer / phase difference expression layer, or may have a layer structure of a substrate film / phase difference expression layer.

[0091] Figure 3 This is a schematic cross-sectional view showing an example of the layer structure of the laminated body prepared in the preparation step in the present embodiment. Figure 3The laminate shown has a layer structure of substrate film 41 / orientation layer 32 / phase difference expressing layer 31, and the phase difference layer 30 is composed of the phase difference expressing layer 31 and the orientation layer 32. As the laminate prepared in this step, one commercial product or a combination of a plurality of commercial products can be used.

[0092] The laminated body prepared in this step may include a substrate film and a phase difference layer laminated in contact with the substrate film, and is not limited to Figure 3 In this laminate, one or more layers other than the base film 41 and the phase difference layer 30 may be laminated. For example, a phase difference layer laminate including the base film 41, the phase difference layer 30 and other phase difference layers may be prepared in this step.

[0093] The substrate film, the phase difference layer, the phase difference expressing layer, the orientation layer, the phase difference layer laminate, and the like will be described in detail in the section of <Optical laminate> to be described later.

[0094] 〔2〕Peeling process

[0095] This step is a step of peeling the base film 41 from the retardation layer 30 at a peeling speed of 50 m / min or more.

[0096] The peeling speed is preferably 60 m / min or more, more preferably 70 m / min or more, further preferably 80 m / min or more, and particularly preferably 90 m / min or more, from the viewpoint of more effectively suppressing the generation of wrinkle defects. The peeling speed is usually 150 m / min or less, and is preferably 120 m / min or less from the viewpoint of preventing the breakage of the substrate film.

[0097] The peeling angle of the base film 41 with respect to the laminated body from which the base film 41 is peeled is usually greater than 90 degrees and less than or equal to 180 degrees. In order to facilitate peeling of the base film 41, the peeling angle is preferably greater than or equal to 120 degrees and less than or equal to 180 degrees.

[0098] The peeling angle refers to the angle formed between the surface direction or conveying direction of the laminate when the base film 41 is peeled and the surface direction or conveying direction of the base film 41 to be peeled.

[0099] When the laminate prepared in the preparation step includes the base film 41, the orientation layer 32, and the phase difference expression layer 31, when the base film 41 is peeled off, when the orientation layer 32 and the base film 41 are peeled off together, the surface of the phase difference expression layer 31 is exposed on the surface of the laminate through this step. When the orientation layer 32 is not peeled off and remains on the laminate side, the surface of the orientation layer 32 is exposed on the surface of the laminate.

[0100] When the laminated body prepared in the preparation step has the base film 41 and the phase difference expressing layer 31 and does not have the orientation layer 32 , the surface of the phase difference expressing layer 31 is exposed on the surface of the laminated body by this step.

[0101] 〔3〕Lamination process

[0102] This step is a step of laminating the optical film 10 on the peeled surface (exposed surface) of the phase difference layer 30 after peeling off the base film 41 via the active energy ray-curable adhesive layer (adhesive layer) 20. Figure 1 The release surface may be the surface of the orientation layer 32 or the surface of the phase difference expressing layer 31. As the active energy ray-curable adhesive, an adhesive having the ability to bond the phase difference layer 30 and the optical film 10 is used.

[0103] In the lamination step, the optical film 10, the adhesive layer 20, and the phase difference layer 30 are laminated so that the adhesive layer 20 is in contact with the phase difference layer 30. Preferably, the optical film 10, the adhesive layer 20, and the phase difference layer 30 are laminated so that the adhesive layer 20 is in contact with the phase difference layer 30.

[0104] The lamination process can be performed by forming an adhesive layer 20 on one or more surfaces selected from the adhesive surface of the optical film 10 and the adhesive surface (release surface) of the phase difference layer 30, and laminating the optical film 10 and the phase difference layer 30 via the adhesive layer 20. The adhesive layer 20 can be formed by applying an active energy ray-curable adhesive to the adhesive surface by a known application method.

[0105] In the laminated body obtained by the lamination process, the thickness of the adhesive layer 20 is usually greater than 0.5 μm and less than 50 μm. From the viewpoint of suppressing wrinkle defects, the viewpoint of adhesion between the optical film 10 and the phase difference layer 30, and the viewpoint of thinning the obtained optical laminated body, it is preferably greater than 1 μm and less than 30 μm, and more preferably greater than 2 μm and less than 20 μm.

[0106] Before forming the adhesive layer 20, one or more surfaces selected from the adhesive surface of the optical film 10 and the adhesive surface (release surface) of the phase difference layer 30 may be subjected to a surface activation treatment such as plasma treatment, corona treatment, ultraviolet irradiation treatment, flame treatment, or saponification treatment.

[0107] This surface activation treatment can improve the adhesion between the optical film 10 and the phase difference layer 30 .

[0108] The optical film 10 may be a film of a single-layer structure or a film of a multi-layer structure. Examples of the optical film 10 include a linear polarizing plate and the like.

[0109] When the optical film 10 is a linear polarizing plate, in the laminate obtained by the lamination step, the linear polarizer included in the linear polarizing plate and the adhesive layer 20 are preferably in contact with each other.

[0110] The optical film 10 and the active energy ray-curable adhesive will be described in more detail in the section of <Optical laminated body> described later.

[0111] According to the production method according to the present embodiment including the above-described peeling step and laminating step, it is possible to produce an optical layered body that is unlikely to suffer from wrinkle defects even when bent with a small radius of curvature. This is presumably due to the following reasons.

[0112] If the base film 41 is peeled off from the phase difference layer 30 at a peeling speed of 50 m / min or more in the peeling process, the surface (peeling surface) of the phase difference layer 30 after peeling becomes rough. Such roughness on the surface of the phase difference layer 30 improves the adhesion with the adhesive layer 20 when the adhesive layer 20 is laminated and brought into contact with the surface in the subsequent lamination process.

[0113] When the above-mentioned adhesion strength is improved, the cured adhesive layer (adhesive layer after curing) and the phase difference layer 30 are deformed integrally when the optical laminate is bent, and thus it is considered that the occurrence of wrinkle defects is easily suppressed.

[0114] The production method according to the present embodiment is also advantageous in suppressing rainbow unevenness described later in the obtained optical layered body.

[0115] In this embodiment, as a means for roughening the surface of the phase difference layer 30, the peeling speed of the base film 41 is controlled. As another means for roughening, for example, a base film whose at least one surface is roughened in advance can be used, and the phase difference layer 30 is formed on the roughened surface to produce a laminate prepared in the preparation step.

[0116] The surface of the base film 41 can be roughened by rubbing the surface or the like.

[0117] 〔4〕Curing process

[0118] In this step, the adhesive layer 20 is cured by irradiation with active energy rays to form a cured adhesive layer 20a, thereby obtaining a Figure 2 An optical laminate having the same layer structure. Regarding this step, the description of the curing step in Embodiment 1 is cited.

[0119] <Optical laminate>

[0120] refer to Figure 2The optical laminate involved in the present invention (hereinafter also simply referred to as "optical laminate") includes them in the order of an optical film 10, a cured adhesive layer 20a which is a cured layer of an active energy ray-curable adhesive, and a phase difference layer 30 including a phase difference expressing layer (a cured layer of a polymerizable liquid crystal compound).

[0121] The optical laminate can be suitably used in image display devices such as organic EL display devices.

[0122] In the optical laminate, the cured adhesive layer 20a is in contact with the phase difference layer 30. In the optical laminate, it is preferred that the optical film 10 is in contact with the cured adhesive layer 20a.

[0123] The optical laminate has a surface ( Figure 2 The surface Xa) in the embodiment satisfies any one or more of the following (a) to (d):

[0124] (a) Arithmetic mean roughness Sa is 0.065 μm or more,

[0125] (b) The root mean square height Sq is 0.085 μm or more,

[0126] (c) the interface development area ratio Sdr is 0.2% or more,

[0127] (d) The root mean square tilt Sdq is greater than or equal to 0.065.

[0128] The arithmetic mean roughness Sa, the root mean square height Sq, the interface development area ratio Sdr, and the root mean square slope Sdq are all indices representing the roughness of a surface, and are measured according to ISO25178 by the method described in the section [Examples].

[0129] Since the optical laminated body of the present invention satisfies any one or more of the above (a) to (d), it is difficult to produce wrinkle defects even if it is bent with a small radius of curvature. This is considered to be because the roughness of the surface on the side of the cured adhesive layer 20a in the phase difference layer 30 improves the adhesion between the cured adhesive layer 20a and the phase difference layer 30, so the cured adhesive layer 20 and the phase difference layer 30 become one and deform when the optical laminated body is bent.

[0130] In addition, an optical laminate satisfying any one or more of the above (a) to (d) is advantageous in that rainbow unevenness can be suppressed in reflected light when viewed from the surface of the optical film 10. The ability to suppress rainbow unevenness is advantageous in improving the visual recognition of an image display device such as an organic EL display device when the optical laminate is used in the device.

[0131] The reason why the optical layered body satisfying any one or more of the above (a) to (d) can suppress rainbow unevenness is considered to be that the interference of reflected light caused by light incident into the optical layered body being reflected at the interface between the layers can be suppressed.

[0132] An optical layered body satisfying any one or more of the above-mentioned (a) to (d) can be suitably produced by the production method according to the present invention described in the above-mentioned section <Production method of optical layered body>.

[0133] In order to more effectively suppress the occurrence of wrinkle defects and rainbow unevenness, the optical layered body preferably satisfies any two or more of the above (a) to (d), more preferably satisfies any three or more of the above (a) to (d), and further preferably satisfies all of the above (a) to (d).

[0134] The arithmetic mean roughness Sa in (a) is preferably 0.067 μm or more, and more preferably 0.070 μm or more, from the viewpoint of more effectively suppressing the generation of wrinkle defects and rainbow unevenness. The arithmetic mean roughness Sa is usually 0.200 μm or less, and is preferably 0.150 μm or less from the viewpoint of reducing the internal haze of the optical laminate to ensure transparency and maintain light transmittance.

[0135] The root mean square height Sq in (b) is preferably 0.087 μm or more, and more preferably 0.090 μm or more, from the viewpoint of more effectively suppressing the generation of wrinkle defects and rainbow unevenness. The root mean square height Sq is usually 0.250 μm or less, and is preferably 0.200 μm or less from the viewpoint of reducing the internal haze of the optical laminate to ensure transparency and maintain light transmittance.

[0136] The interface development area ratio Sdr in (c) is preferably 0.25% or more, and more preferably 0.3% or more, from the viewpoint of more effectively suppressing the generation of wrinkle defects and rainbow unevenness. The interface development area ratio Sdr is usually 1.20% or less, and is preferably 1.10% or less from the viewpoint of reducing the internal haze of the optical laminate to ensure transparency and maintain light transmittance.

[0137] The root mean square tilt Sdq in (d) is preferably 0.070 or more, and more preferably 0.072 or more, from the viewpoint of more effectively suppressing the generation of wrinkle defects and rainbow unevenness. The root mean square tilt Sdq is usually 0.180 or less, and is preferably 0.160 or less from the viewpoint of reducing the internal haze of the optical laminate to ensure transparency and maintain light transmittance.

[0138] The elements that constitute or can constitute the optical layered body will be described below.

[0139] 〔1〕Optical films

[0140] As described above, the optical film 10 may be a film having a single-layer structure or a film having a multi-layer structure.

[0141] Examples of the optical film 10 include a linear polarizing plate and a linear polarizing plate.

[0142] 〔2〕Linear polarization plate

[0143] The linear polarizing plate is an optical element including at least a linear polarizer, and may further include a thermoplastic resin film bonded to at least one surface of the linear polarizer. The so-called linear polarizer refers to an optical element having the property of transmitting linear polarized light having a vibration plane orthogonal to the absorption axis when non-polarized light is incident.

[0144] The linear polarizer may be obtained by, for example, adsorbing and aligning a dichroic pigment such as iodine on a product obtained by aligning a polyvinyl alcohol resin film. The linear polarizer may be a polarizer obtained by adsorbing and aligning a dichroic pigment on a single-layer polyvinyl alcohol resin film (a resin film in which polyvinyl alcohol molecules contained in the polyvinyl alcohol resin film are oriented), or may be a laminated film of two or more layers of a polyvinyl alcohol resin layer in which a dichroic pigment is adsorbed and oriented on a substrate film. Such a linear polarizer can be manufactured by various methods known in the art.

[0145] The thickness of the linear polarizing plate formed by adsorption and orientation of the dichroic dye on a single-layer polyvinyl alcohol resin film is preferably 20 μm or less, more preferably 15 μm or less, and further preferably 10 μm or less.

[0146] The linear polarizer can also be a cured film in which a dichroic pigment is oriented on a polymerizable liquid crystal compound and the polymerizable liquid crystal compound is polymerized. Usually, a composition containing a polymerizable liquid crystal compound and a dichroic pigment is applied to a substrate film composed of a thermoplastic resin film or an orientation layer provided thereon and dried, and the polymerizable liquid crystal compound contained in the applied film is polymerized and cured by irradiation with active energy rays such as ultraviolet rays, thereby obtaining the linear polarizer. The laminate of the substrate film and the linear polarizer (cured film) thus obtained can be used as a linear polarizer.

[0147] The thickness of the substrate film for forming the cured film is not particularly limited, but is generally preferably 1 μm to 300 μm, more preferably 10 μm to 200 μm, and further preferably 30 μm to 120 μm from the viewpoint of workability such as strength and handling.

[0148] In the linear polarizing plate, examples of the thermoplastic resin film bonded to at least one side of the linear polarizing plate include resin films composed of polyolefin resins such as polyethylene and polypropylene; cyclic polyolefin resins such as norbornene polymers; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; (meth)acrylic resins such as poly(methyl)acrylate; cellulose ester resins such as triacetyl cellulose, diacetyl cellulose and cellulose acetate propionate; vinyl alcohol resins such as polyvinyl alcohol and polyvinyl acetate; polycarbonate resins; polystyrene resins; polyarylate resins; polysulfone resins; polyethersulfone resins; polyamide resins; polyimide resins; polyether ketone resins; polyphenylene sulfide resins; polyphenylene ether resins, and mixtures and copolymers thereof.

[0149] Among the above-mentioned resins, any one of cyclic polyolefin-based resins, polyester-based resins, cellulose ester-based resins, and (meth)acrylic-based resins, or a mixture thereof is preferably used.

[0150] In addition, "(meth)acrylic acid" means "at least one of acrylic acid and methacrylic acid".

[0151] The thermoplastic resin film may be a single layer in which one or more resin materials are mixed, or may have a multilayer structure of two or more layers. In the case of a multilayer structure, the resins constituting each layer may be the same or different from each other.

[0152] Any additives may be added to the thermoplastic resin film, such as ultraviolet absorbers, antioxidants, lubricants, plasticizers, mold release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.

[0153] The thickness of the thermoplastic resin film is preferably from 2 μm to 300 μm, more preferably from 5 μm to 200 μm, further preferably from 5 μm to 100 μm, further preferably from 5 μm to 50 μm, and particularly preferably from 5 μm to 30 μm, from the viewpoint of thinning and flexibility of the optical layered body and durability of the optical layered body.

[0154] The thermoplastic resin film can be laminated on the linear polarizer via an adhesive layer.

[0155] Examples of the adhesive that forms the adhesive layer include water-based adhesives and active energy ray-curable adhesives.

[0156] Examples of the water-based adhesive include a polyvinyl alcohol-based resin aqueous solution and a water-based two-component urethane latex adhesive.

[0157] The active energy ray-curable adhesive is an adhesive that is cured by irradiation with active energy rays such as ultraviolet rays, and examples thereof include adhesives containing polymerizable compounds and photopolymerization initiators, adhesives containing photoreactive resins, adhesives containing binder resins and photoreactive crosslinking agents, etc. As the above-mentioned polymerizable compounds, photopolymerizable monomers such as photocurable epoxy monomers, photocurable (meth) acrylic monomers, and photocurable urethane monomers, and oligomers derived from these monomers, etc. can be cited. As the above-mentioned photopolymerization initiator, a photopolymerization initiator containing a substance that generates active species such as neutral free radicals, anionic free radicals, and cationic free radicals by irradiation with active energy rays such as ultraviolet rays can be cited.

[0158] The linear polarizing plate can further include other films or layers other than those mentioned above. As other films or layers, a protective film laminated on the surface of the linear polarizing plate can be cited; a reflective film, a semi-transmissive reflective film, an optical compensation film, a film with an anti-glare function, a phase difference film, etc. arranged at a suitable position of the linear polarizing plate.

[0159] The linear polarizing plate is preferably Figure 4 As shown in FIG. 1 , a sheet protective polarizing plate having a thermoplastic resin film is bonded to only one side of the linear polarizing plate. If the linear polarizing plate is a sheet protective polarizing plate, the thickness of the optical laminate can be reduced as a result because the thickness of the linear polarizing plate is thin. Therefore, for example, an organic EL display device having the optical laminate of the present invention can be easily used as a flexible organic EL display device that can be bent, folded, rolled, etc.

[0160] When the optical film 10 is a sheet protective polarizing plate, in the optical laminate, the linear polarizing plate is preferably in contact with the cured adhesive layer 20 a .

[0161] [3] Curing the adhesive layer

[0162] The cured adhesive layer 20a is a cured product layer of an active energy ray-curable adhesive. The cured adhesive layer 20a can be formed by curing the active energy ray-curable adhesive layer (adhesive layer) 20 formed in the above-mentioned lamination step in a curing step.

[0163] As the active energy ray-curable adhesive, the same adhesive as the active energy ray-curable adhesive described in the above [2] can be used.

[0164] In the optical laminate, the thickness of the cured adhesive layer 20a is generally greater than 0.5 μm and less than 50 μm. From the viewpoint of suppressing wrinkle defects, the adhesion between the optical film 10 and the phase difference layer 30, and the thinning of the obtained optical laminate, it is preferably greater than 1 μm and less than 30 μm, and more preferably greater than 2 μm and less than 20 μm.

[0165] 〔4〕Phase difference layer

[0166] The phase difference layer 30 includes a phase difference expressing layer 31 which is a cured layer of a polymerizable liquid crystal compound, and may further include an alignment layer 32 .

[0167] The phase difference expression layer 31 is formed using a polymerizable liquid crystal compound, and as the polymerizable liquid crystal compound, a known polymerizable liquid crystal compound can be used. The type of polymerizable liquid crystal compound is not particularly limited, and a rod-shaped liquid crystal compound, a disc-shaped liquid crystal compound, and a mixture thereof can be used. The polymerizable liquid crystal compound used to form a 1 / 4 wavelength plate with reverse wavelength dispersion is preferably a rod-shaped liquid crystal compound, for example, a polymerizable liquid crystal compound described in JP Patent Publication No. 2011-207765.

[0168] A phase difference expression layer forming composition containing a polymerizable liquid crystal compound and a solvent and various additives as needed is applied on the orientation layer 32 to form a coating film, and the coating film is cured to form a phase difference expression layer 31 as a cured layer of the polymerizable liquid crystal compound. Alternatively, the phase difference expression layer forming composition can be directly applied on the substrate film to form a coating film, and the coating film and the substrate film are stretched together to form the phase difference expression layer 31.

[0169] The thickness of the phase difference expression layer 31 is usually 0.1 μm or more and 10 μm or less, and preferably 0.2 μm or more and 5 μm or less.

[0170] In addition to the above-mentioned polymerizable liquid crystal compound and solvent, the phase difference expression layer forming composition may further include a polymerization initiator, a reactive additive, a leveling agent, a polymerization inhibitor, etc. The polymerizable liquid crystal compound, solvent, polymerization initiator, reactive additive, leveling agent, polymerization inhibitor, etc. can be appropriately used those known.

[0171] As the leveling agent that can be included in the phase difference performance layer forming composition and the phase difference performance layer, there can be cited a leveling agent with organic modified silicone oil as the main component, a leveling agent with polyacrylate compounds as the main component, and a leveling agent with fluorine atom-containing compounds such as perfluoroalkyl as the main component. The so-called main component is the component with the largest amount of all the components contained in the leveling agent. The content of the leveling agent in the phase difference performance layer forming composition is preferably 0.01 mass parts or more and 5 mass parts or less relative to 100 mass parts of the polymerizable liquid crystal compound, and more preferably 0.1 mass parts or more and 3 mass parts or less.

[0172] The orientation layer 32 that can be included in the phase difference layer 30 is a layer having an orientation constraint force that causes the polymerizable liquid crystal compound contained in the liquid crystal layer formed thereon to orient the liquid crystal in a desired direction. Examples of the orientation layer 32 include an orientation polymer layer formed of an orientation polymer, a photo-orientation polymer layer formed of a photo-orientation polymer, and a groove orientation layer having a concave-convex pattern and a plurality of grooves (grooves) on the surface of the layer.

[0173] The thickness of the alignment layer 32 is usually greater than or equal to 10 nm and less than or equal to 500 nm, and preferably greater than or equal to 10 nm and less than or equal to 200 nm.

[0174] The oriented polymer layer can be formed by applying a composition in which an oriented polymer is dissolved in a solvent to the base film 41, removing the solvent, and performing a rubbing treatment as needed. In this case, the orientation restraining force can be arbitrarily adjusted according to the surface state of the oriented polymer and the rubbing conditions.

[0175] The photo-aligned polymer layer can be formed by applying a composition containing a polymer or monomer having a photoreactive group and a solvent to the base film 41 and irradiating the substrate film 41 with polarized light. In this case, the orientation restraining force in the photo-aligned polymer layer can be arbitrarily adjusted by, for example, the polarized light irradiation conditions for the photo-aligned polymer.

[0176] The groove orientation layer can be formed by the following methods, etc.: exposing and developing the surface of a photosensitive polyimide film through an exposure mask having a slit in a pattern shape to form a concave-convex pattern; forming an uncured layer of an active energy ray-curable resin on a plate-shaped master sheet having grooves on the surface, transferring the layer to a substrate film 41 and curing it; forming an uncured layer of an active energy ray-curable resin on the substrate film 41, forming concave-convex by pushing a roller-shaped master sheet having concave-convex against the layer, etc., and curing it.

[0177] As the base film 41 , a resin film having the same structure as the above-mentioned thermoplastic resin film can be used.

[0178] The thickness of the base film 41 is not particularly limited, but is generally preferably 1 μm to 300 μm, more preferably 10 μm to 200 μm, and further preferably 30 μm to 120 μm from the viewpoint of strength, handling and other workability.

[0179] Any additives may be added to the base film 41. Examples of the additives include ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.

[0180] [5] Phase difference layer stack

[0181] As described above, in the lamination step of the first embodiment and the preparation step of the second embodiment involved in the method for manufacturing an optical layered body, as the phase difference layer 30, a phase difference layer laminate can be used, which includes a phase difference layer laminate including the phase difference layer 30 and another phase difference layer.

[0182] Figure 5 It is a schematic cross-sectional view showing an example of the layer structure of the phase difference laminate. Figure 5 The phase difference laminate shown in the figure includes a base film 41, an orientation layer 32, a phase difference expressing layer 31, an adhesive layer 61, a phase difference expressing layer 71, an orientation layer 72, and a base film 42 in this order. Figure 5 In the illustrated phase difference laminate, the phase difference expressing layer 31 and the orientation layer 32 can serve as the phase difference layer 30 bonded to the optical film 10 via the cured adhesive layer 20 a in the optical laminate.

[0183] exist Figure 5 In the phase difference stacked body shown, at least one of the orientation layer 32 and the orientation layer 72 may be absent.

[0184] exist Figure 5 In the phase difference laminate shown, the combination of the phase difference expression layer 31 and the phase difference expression layer 71 is, for example, a combination of a half-wave plate and a quarter-wave plate, or a combination of a quarter-wave plate with reverse wavelength dispersion and a positive C plate.

[0185] In the case of a combination of a half-wavelength plate and a quarter-wavelength plate, it is preferred that the phase difference expressing layer 31 disposed on the side closer to the optical film 10 in the optical laminate is a half-wavelength plate.

[0186] Use in the lamination step of the first embodiment or the second embodiment of the method for producing an optical layered body Figure 5 In the case of the phase difference laminate shown, the phase difference laminate is laminated on the optical film 10 via the adhesive layer 20 after the base film 41 is peeled off.

[0187] Figure 6 It means that the optical layer is used in the lamination process of the first embodiment or the second embodiment of the method for producing the optical layered body. Figure 5 The phase difference laminate shown is a schematic cross-sectional view of an example of the layer structure of an optical laminate produced. Figure 6 In the optical laminate shown, at least one of the alignment layer 32 and the alignment layer 72 may be absent.

[0188] For example, a laminate having a layer structure of substrate film 41 / orientation layer 32 / phase difference expression layer 31 and a laminate having a layer structure of substrate film 42 / orientation layer 72 / phase difference expression layer 71 can be prepared or prepared, and these laminates can be bonded together via adhesive layer 61 to produce Figure 5 The phase difference stack shown.

[0189] Examples of the adhesive forming the adhesive layer 61 include water-based adhesives and active energy ray-curable adhesives. As these adhesives, the same adhesives as those used for bonding the linear polarizer and the thermoplastic resin film can be used.

[0190] An adhesive layer can also be used as the bonding layer 61. As the adhesive composition forming the adhesive layer, there can be cited compositions obtained by adding a crosslinking agent such as an isocyanate compound, an epoxy compound, or an aziridine compound to a (meth)acrylic resin, a styrene resin, or a silicone resin as a base polymer.

[0191] The adhesive layer 61 is preferably a cured layer of an active energy ray-curable adhesive such as an ultraviolet-curable adhesive, from the viewpoint of more effectively suppressing the occurrence of wrinkle defects.

[0192] [6] Adhesive layer

[0193] The optical laminate can further include an adhesive layer. Figure 7 It is a schematic cross-sectional view showing an example of the layer structure of an optical laminate having a pressure-sensitive adhesive layer 80 .

[0194] Figure 7 The optical stack shown can be obtained, for example, from Figure 6 The optical laminate shown is produced by peeling the base film 42 and laminating the adhesive layer on the peeled surface. A separator film may be laminated on the outer surface of the adhesive layer.

[0195] Example

[0196] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.

[0197] <Example 1>

[0198] (1) Fabrication of linear polarizing plate

[0199] A linear polarizing plate (thickness: 8 μm) was prepared as a uniaxially stretched film in which iodine was adsorbed and oriented on a polyvinyl alcohol-based resin film.

[0200] A first thermoplastic resin film is laminated on one surface of the linear polarizer via a polyvinyl alcohol-based adhesive, and a second thermoplastic resin film is laminated on the other surface of the linear polarizer, and the laminate is passed between a pair of laminating rollers to obtain a laminate having a layer structure of first thermoplastic resin film / polyvinyl alcohol-based adhesive layer / linear polarizer / second thermoplastic resin film.

[0201] An adhesive is not interposed between the linear polarizer and the second thermoplastic resin film, and the second thermoplastic resin film is laminated on the linear polarizer in a releasable manner.

[0202] As the first thermoplastic resin film and the second thermoplastic resin film, the following thermoplastic resin films were used.

[0203] First thermoplastic resin film: a transparent hard coating film manufactured by Nippon Paper Industries, Ltd., trade name "COP20ST-HC" (a film having a transparent hard coating layer formed on a cyclic polyolefin resin film, thickness: 25 μm)

[0204] Second thermoplastic resin film: triacetyl cellulose (TAC) film manufactured by Fujifilm Corporation (trade name “FUJITAC”) (thickness: 80 μm)

[0205] The obtained laminate was subjected to a heat treatment at 80° C. for 300 seconds using a hot air dryer to dry the polyvinyl alcohol-based adhesive layer, thereby obtaining a linear polarizing plate.

[0206] (2) Preparation of Phase Difference Layer Laminate

[0207] The retardation films 1 and 2 and the active energy ray-curable adhesive 1 shown below were prepared.

[0208] Phase difference film 1 as a half-wavelength plate: "QL FILM QL AA318" manufactured by Fujifilm Corporation (a phase difference film having a total thickness of 2 μm, comprising a substrate film 1 as a TAC film having a thickness of 80 μm, an orientation layer 1 formed thereon, and a phase difference expression layer 1 (in-plane phase difference value of 235 nm) as a cured product layer (single layer) of a polymerizable liquid crystal compound formed thereon)

[0209] Phase difference film 2 as a quarter wavelength plate: "QL FILM QL AB318" manufactured by Fujifilm Corporation (a phase difference film having a total thickness of 1 μm, which is composed of a substrate film 2 as a TAC film having a thickness of 80 μm, an orientation layer 2 formed thereon, and a phase difference expression layer 2 (in-plane phase difference value of 120 nm) as a cured product layer (single layer) of a polymerizable liquid crystal compound formed thereon)

[0210] Active energy ray-curable adhesive 1: Cationic polymerizable ultraviolet-curable high-refractive index adhesive

[0211] The surface of the phase difference expression layer 1 of the phase difference film 1 and the surface of the phase difference expression layer 2 of the phase difference film 2 were subjected to corona treatment. The above-mentioned active energy ray-curable adhesive 1 was applied on the corona-treated surface of each of these phase difference films using a rod coater so that the total thickness of the adhesive layer after curing was 1.5 μm, and then the phase difference film 1 and the phase difference film 2 were overlapped and passed through a pair of laminating rollers to obtain a laminate having a layer structure of substrate film 1 / orientation layer 1 / phase difference expression layer 1 / active energy ray-curable adhesive 1 layer / phase difference expression layer 2 / orientation layer 2 / substrate film 2.

[0212] The obtained laminate was irradiated with ultraviolet rays using an ultraviolet irradiation device (the lamp used was "DBULB" manufactured by Fusion UV Systems) so that the accumulated light intensity was 250 mJ / cm 2 (UVB)) to cure the layer of the active energy ray-curable adhesive 1, thereby obtaining a phase difference layer laminate.

[0213] (3) Preparation of Optical Laminated Body 1

[0214] The second thermoplastic resin film of the linear polarizing plate obtained in (1) was peeled off, and the base film 1 and the orientation layer 1 of the phase difference layer laminated body obtained in (2) were peeled off at a peeling speed of 25 m / min. The peeling angle of the base film 1 with respect to the phase difference layer laminated body from which the base film 1 was peeled off was set to 180 degrees.

[0215] The surface of the linear polarizing plate exposed by peeling off the second thermoplastic resin film and the surface of the phase difference expressing layer 1 exposed by peeling off the base film 1 were subjected to corona treatment.

[0216] In addition, the orientation layer 1 and the base film 1 are peeled and removed together.

[0217] An active energy ray-curable adhesive 2 is applied to the corona-treated surfaces of the linear polarizing plate and the phase difference layer stack using a rod coater so that the total thickness of the adhesive layer after curing becomes 2 μm. The linear polarizing plate and the phase difference layer stack are then overlapped and passed between a pair of laminating rollers to obtain a stack having a layer structure of a first thermoplastic resin film / polyvinyl alcohol-based adhesive layer / linear polarizer / layer of active energy ray-curable adhesive 2 / phase difference expression layer 1 / cured layer of active energy ray-curable adhesive 1 / phase difference expression layer 2 / orientation layer 2 / base film 2.

[0218] As the active energy ray-curable adhesive 2, the following adhesive was used.

[0219] Active energy ray-curable adhesive 2: Cationic polymerizable ultraviolet-curable adhesive

[0220] The obtained laminate was placed in a constant temperature and humidity chamber and maintained (left to stand) for 5 hours in an environment at a temperature of 40° C. (maintaining step). The relative humidity in the maintaining step was 55% RH (the same also applies to other Examples and Comparative Examples).

[0221] Then, the laminate was irradiated with ultraviolet rays using an ultraviolet irradiation device (the lamp used was "HBULB" manufactured by Fusion UV Systems) so that the accumulated light intensity was 400 mJ / cm 2 (UVB)) was applied to cure the active energy ray-curable adhesive 2 layer, thereby obtaining an optical laminate 1. The environment during ultraviolet irradiation was set to a temperature of 23° C. and a relative humidity of 55% RH (the same also applies to other Examples and Comparative Examples).

[0222] In the obtained optical laminate 1, the angle of the phase-advancing axis SL1 of the phase difference expression layer 1 (1 / 2 wavelength plate) relative to the absorption axis PL of the linear polarizer is 75°, and the angle of the phase-advancing axis SL2 of the phase difference expression layer 2 (1 / 4 wavelength plate) relative to the absorption axis PL of the linear polarizer is 15°. The optical laminate 1 functions as a circular polarizer.

[0223] (4) Preparation of Optical Layered Body 2 (Lamination of Adhesive Layer on Optical Layered Body 1)

[0224] The following sheet-like adhesive 1 was prepared.

[0225] · Sheet-like adhesive 1: Transfer-type carrier-free film (a laminated film having a (meth)acrylic adhesive layer [thickness: 15 μm], a lightly releasable film laminated on one surface thereof, and a heavy releasable film laminated on the other surface thereof)

[0226] The base film 2 and the orientation layer 2 of the optical laminate 1 obtained in the above (3) are peeled off together, and the lightly peelable film of the sheet-like adhesive 1 is peeled off. The surface of the phase difference expression layer 2 exposed by peeling off the base film 2 and the surface of the adhesive layer exposed by peeling off the lightly peelable film are subjected to corona treatment.

[0227] In addition, the orientation layer 2 and the base film 2 are peeled off together.

[0228] An optical laminate 1 and a thin sheet-like adhesive 1 are overlapped and passed between a pair of laminating rollers to obtain an optical laminate 2 having a layer structure of a first thermoplastic resin film / polyvinyl alcohol-based adhesive layer / linear polarizer / cured layer of active energy ray-curable adhesive 2 / phase difference display layer 1 / cured layer of active energy ray-curable adhesive 1 / phase difference display layer 2 / adhesive layer / heavy-peelable film.

[0229] <Example 2>

[0230] An optical laminate 1 was prepared in the same manner as in Example 1, except that the laminate was attached to the inner wall in a constant temperature and humidity chamber and was kept (left to stand) for 5 hours in a vibration environment with a frequency of 10 Hz and an amplitude of 1 mm in the holding step. The temperature environment in the holding step was 23° C. In addition, an optical laminate 2 was prepared in the same manner as in Example 1, except that the optical laminate 1 was used.

[0231] <Example 3>

[0232] An optical laminate 1 was prepared in the same manner as in Example 1, except that the laminate was placed in a constant temperature and humidity chamber and kept (left to stand) at a temperature of 23° C. for 3 days in the holding step. The relative humidity in the holding step was 55% RH. In addition, an optical laminate 2 was prepared in the same manner as in Example 1, except that the optical laminate 1 was used.

[0233] <Example 4>

[0234] (1) Fabrication of linear polarizing plate

[0235] In the same manner as in Example 1, a linear polarizing plate was produced.

[0236] (2) Preparation of Phase Difference Layer Laminate

[0237] In the same manner as in Example 1, a phase difference layer stack was produced.

[0238] (3) Preparation of Optical Laminated Body 1

[0239] The second thermoplastic resin film and the orientation layer 1 of the linear polarizing plate obtained in (1) were peeled off together, and the base film 1 of the phase difference layer laminate obtained in (2) was peeled off at a peeling speed of 90 m / min. The peeling angle of the base film 1 with respect to the phase difference layer laminate from which the base film 1 was peeled was set to 180 degrees.

[0240] Thereafter, the optical layered body 1 was produced in the same manner as in Example 1 except that the holding step was not performed.

[0241] (4) Preparation of Optical Layered Body 2 (Lamination of Adhesive Layer on Optical Layered Body 1)

[0242] An optical layered body 2 was prepared in the same manner as in Example 1 except that the optical layered body 1 obtained in the above (3) was used.

[0243] <Comparative Example 1>

[0244] An optical laminate 1 was prepared in the same manner as in Example 1, except that the laminate was placed in a constant temperature and humidity chamber and kept (left to stand) at a temperature of 23° C. for 5 hours in the holding step. The relative humidity in the holding step was 55% RH. In addition, an optical laminate 2 was prepared in the same manner as in Example 1, except that the optical laminate 1 was used.

[0245] <Comparative Example 2>

[0246] An optical laminate 1 was prepared in the same manner as in Example 1 except that the holding step was not performed and that after obtaining a laminate having a layer structure of first thermoplastic resin film / polyvinyl alcohol-based adhesive layer / linear polarizer / active energy ray-curable adhesive 2 layer / phase difference expressing layer 1 / cured material layer of active energy ray-curable adhesive 1 / phase difference expressing layer 2 / base film 2, ultraviolet rays were immediately irradiated to cure the active energy ray-curable adhesive 2 layer. In addition, an optical laminate 2 was prepared in the same manner as in Example 1 except that the optical laminate 1 was used.

[0247] <Comparative Example 3>

[0248] (1) Preparation of Linear Polarizing Plate with Adhesive Layer

[0249] In the same manner as in Example 1, a linear polarizing plate was produced.

[0250] Furthermore, a sheet-like adhesive 2 shown below was prepared.

[0251] · Sheet-like adhesive 2: Transfer-type carrier-free film (a laminated film having a (meth)acrylic adhesive layer [thickness: 5 μm], a lightly releasable film laminated on one surface thereof, and a heavy releasable film laminated on the other surface thereof)

[0252] The second thermoplastic resin film of the linear polarizing plate is peeled off, and the lightly releasable film of the sheet-like adhesive 2 is peeled off. The surface of the linear polarizing plate exposed by peeling off the second thermoplastic resin film and the surface of the adhesive layer exposed by peeling off the lightly releasable film are subjected to corona treatment.

[0253] Thereafter, a sheet-like adhesive 2 from which the lightly releasable film has been peeled is laminated on the surface (corona-treated surface) of the linear polarizer, thereby obtaining a linear polarizer with an adhesive layer having a layer structure of a first thermoplastic resin film / polyvinyl alcohol-based adhesive layer / linear polarizer / adhesive layer / heavily releasable film.

[0254] (2) Preparation of Phase Difference Layer Laminate

[0255] In the same manner as in Example 1, a phase difference layer stack was produced.

[0256] (3) Preparation of Optical Laminated Body 1

[0257] The heavy-peelable film of the linear polarizing plate with an adhesive layer obtained in (1) was peeled off, and the base film 1 and the orientation layer 1 of the phase difference layer laminated body obtained in (2) were peeled off at a peeling speed of 25 m / min. The peeling angle of the base film 1 with respect to the phase difference layer laminated body from which the base film 1 was peeled was set to 180 degrees.

[0258] The surface of the pressure-sensitive adhesive layer exposed by peeling off the heavy-release film and the surface of the phase difference expression layer 1 exposed by peeling off the base film 1 were subjected to corona treatment.

[0259] In addition, the orientation layer 1 and the base film 1 are peeled and removed together.

[0260] Thereafter, a base film 1 is laminated on the corona-treated surface of the linear polarizing plate with an adhesive layer, thereby obtaining an optical laminate 1 having a layer structure of a first thermoplastic resin film / polyvinyl alcohol-based adhesive layer / linear polarizing plate / adhesive layer / phase difference display layer 1 / cured layer of active energy ray-curable adhesive 1 / phase difference display layer 2 / base film 2.

[0261] (4) Preparation of Optical Layered Body 2 (Lamination of Adhesive Layer on Optical Layered Body 1)

[0262] An optical layered body 2 was prepared in the same manner as in Example 1 except that the optical layered body 1 obtained in the above (3) was used.

[0263] [Measurement / Evaluation]

[0264] (1) Determination of surface roughness

[0265] A rectangular laminate sheet with a length of 50 mm (long side) and a width of 15 mm, with the absorption axis of the linear polarizer as the length direction, is cut out from the optical laminate 2, the heavy peelable film is peeled off to expose the adhesive layer, and the exposed adhesive layer is attached to an acrylic resin plate (black) to make a test piece [having a layer structure of first thermoplastic resin film / polyvinyl alcohol-based adhesive layer / linear polarizer / cured layer of active energy ray-curable adhesive 2 / phase difference expression layer 1 / cured layer of active energy ray-curable adhesive 1 / phase difference expression layer 2 / adhesive layer / acrylic resin plate (black)]. The test piece was irradiated with light from the first thermoplastic resin film side, and the arithmetic mean roughness Sa, root mean square height Sq, interface development area ratio Sdr, and root mean square tilt Sdq of the surface on the linear polarizer side of the phase difference layer (phase difference expression layer 1) of the optical laminate 1 were measured in layer cross section analysis mode by a scanning white interference microscope "VertScan" (manufactured by Hitachi High-Technologies Corporation) in accordance with ISO25178. The results are shown in Table 1. The measurement conditions are as follows.

[0266] Camera: Sony "XCL-32"

[0267] Objective lens: 5CTI

[0268] Lens body: 1.0X

[0269] Zoom lens: 1X

[0270] Light source: 530White

[0271] Measurement device: Piezoelectric

[0272] Measurement mode: Wave

[0273] (2) Evaluation of wrinkle defects

[0274] A test piece (rectangular shape) having a length of 50 mm (long side) and a width of 15 mm (short side) with the absorption axis of the linear polarizing plate as the longitudinal direction was cut out from the optical layered body 1 .

[0275] like Figure 8As shown in FIG. 1 , a 10 mm bending test is performed by repeating the following reduction process and expansion process 10 times: the reduction process bends the test piece (S) so that the two short sides (S1) face each other to form a curved portion (C) in the central portion in the long side direction, and while maintaining this state, it is maintained between two glass plates (flat plates) (G) arranged parallel to each other, and the curvature diameter (R) of the curved portion of the test piece is narrowed to 10 mm by reducing the interval between the two glass plates (G), and the expansion process then expands the interval between the two glass plates until the curved state is eliminated. In addition, the two short sides (S1) of the test piece (S) are respectively fixed to the glass plates (G).

[0276] If wrinkle defects did not occur in the test piece after the 10 mm bending test, the same test piece was subjected to a 5 mm bending test in which the reduction and expansion steps were repeated 10 times except that the curvature diameter R of the bent portion was further set to 5 mm.

[0277] When wrinkle defects did not occur in the test piece after the 5 mm bending test, the same test piece was subjected to a 4 mm bending test in which the reduction and expansion steps were repeated 10 times except that the curvature diameter R of the bent portion was further set to 4 mm.

[0278] If wrinkle defects did not occur in the test piece after the 4 mm bending test, the 3 mm bending test was performed in the same manner as above except that the curvature diameter R of the bent portion was further set to 3 mm by repeating the reduction step and the expansion step 10 times.

[0279] If wrinkle defects did not occur in the test piece after the 3 mm bending test, the same test piece was subjected to a 2 mm bending test in which the reduction and expansion steps were repeated 10 times except that the curvature diameter R of the bent portion was further set to 2 mm.

[0280] The portion of the test piece wound around the centripetal bar was visually observed, and the difficulty of occurrence of wrinkle defects was evaluated according to the following criteria.

[0281] A: No wrinkle defects were observed from the start of the 10 mm bending test to the end of the 2 mm bending test.

[0282] B: Starting from the 10 mm bending test, no wrinkle defects are seen after the 3 mm bending test. However, if the 2 mm bending test is continued, wrinkle defects will occur.

[0283] C: No wrinkle defects were observed after the 4mm bending test, starting from the 10mm bending test. However, wrinkle defects occurred after the 3mm bending test.

[0284] In addition, the absorption axis (PL) of the linear polarizer, the leading axis (SL1) of the phase difference expression layer 1, and the leading axis (SL2) of the phase difference expression layer 2 in each test piece are as follows when viewed from the linear polarizer side: Fig. 9 That is, when viewed from the first thermoplastic resin film side (linear polarizer side), the left-hand rotation is set as positive (+), the absorption axis (PL) is +135° relative to the short side, the phase-advancing axis (SL1) is +60° relative to the short side, and the phase-advancing axis (SL2) is +120° relative to the short side. Each test piece functions as a circular polarizing plate.

[0285] (3) Evaluation of rainbow unevenness

[0286] A test piece (rectangular) of 100 mm in length and 100 mm in width was cut out from the optical laminate 2. The heavy peelable film was peeled off from the test piece, and the exposed adhesive layer was bonded to a flat black acrylic resin plate. In addition, a glass plate (alkali-free glass "EAGLE XG" manufactured by Corning, thickness 0.7 mm) was laminated on the first thermoplastic resin film, which was the top layer of the optical laminate 2, through a water film to prepare a laminate for evaluation.

[0287] The obtained evaluation laminate is placed in a room with a fluorescent lamp on. The position of the fluorescent lamp is set to a height of 250 mm from the black acrylic resin plate. In this state, the reflected light from the fluorescent lamp is visually observed from the surface (surface on the glass plate side) of the evaluation laminate, and the difficulty of generating rainbow unevenness is evaluated according to the following criteria. The results are shown in Table 1. The so-called reflected light from the fluorescent lamp refers to the light from the fluorescent lamp incident on the interior of the optical laminate 2, which is reflected at the interface of each layer and emitted from the glass plate side.

[0288] A: No iridescence is visible in reflected light.

[0289] B: The rainbow-like unevenness can be seen extremely slightly in the reflected light.

[0290] C: Rainbow unevenness is seen in reflected light (rainbow unevenness is seen more clearly than in B).

[0291] [Table 1]

[0292]

[0293] Description of Reference Numerals

[0294] 10 Optical films,

[0295] 20 active energy ray-curable adhesive layer (adhesive layer),

[0296] 20a Curing the adhesive layer,

[0297] 30 phase difference layer,

[0298] 31 Phase difference expression layer,

[0299] 32 Orientation layer,

[0300] 41 substrate film,

[0301] 42 substrate film,

[0302] 50 Linear polarizer,

[0303] 51 adhesive layer,

[0304] 52 Thermoplastic resin film,

[0305] 61 adhesive layer,

[0306] 71 Phase difference expression layer,

[0307] 72 Orientation layer,

[0308] 80 adhesive layer.

Claims

1. A method for producing an optical laminate, characterized in that: The optical laminate includes an optical film, a cured adhesive layer which is a cured layer of an active energy ray-curable adhesive, and a retardation layer which is a cured layer of a polymerizable liquid crystal compound in this order. The manufacturing method comprises the following steps in the following order: A step of laminating the optical film, the active energy ray-curable adhesive layer, and the phase difference layer so that the active energy ray-curable adhesive layer and the phase difference layer are in contact with each other; A step of maintaining the device under the condition that any one of the following (1) to (3) is satisfied: (1) Keep at a temperature above 30°C for more than 2 hours. (2) Maintain the vibration for more than 2 hours at a frequency of 5 Hz or more and an amplitude of 0.5 mm or more. (3) Maintained for more than 48 hours; and A step of curing the active energy ray-curable adhesive layer to form the cured adhesive layer.

2. The method for producing an optical layered body according to claim 1, wherein: The optical film includes a linear polarizer.

3. The method for producing an optical layered body according to claim 2, wherein: In the lamination step, the optical film, the active energy ray-curable adhesive layer, and the phase difference layer are laminated so that the linear polarizer and the active energy ray-curable adhesive layer are in contact with each other.

Citation Information

Patent Citations

  • Compound, optical film and method for producing optical film

    JP2011207765A

  • Polarizing plate with retardation layer and organic el display device

    JP2018017996A

  • Pressure-sensitive adhesive, pressure-sensitive adhesive sheet and optical film with pressure-sensitive adhesive

    JP2009019172A

  • Composite retardation plate, optical laminate, and image display device

    JP2019091029A